Queer globalizations: citizenship and the afterlife of colonialism - Cruz, Arnaldo; Manalansan, Martin F. (Sexual cultures, 2002)
Globalization has a taste for queer cultures. Whether in advertising, film, performance art, the internet, or in the political discourses of human rights in emerging democracies, queerness sells and the transnational circulation of peoples, identities and social movements that we call "globalization" can be liberating to the extent that it incorporates queer lives and cultures. From this perspective, globalization is seen as allowing the emergence of queer identities and cultures on a global scale. The essays in Queer Globalizations bring together scholars of postcolonial and lesbian and gay studies in order to examine from multiple perspectives the narratives that have sought to define globalization. In examining the tales that have been spun about globalization, these scholars have tried not only to assess the validity of the claims made for globalization, they have also attempted to identify the tactics and rhetorical strategies through which these claims and through which global circulation are constructed and operate.
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; racisme; régions géographiques; sexualité; shm4000; système colonial; systèmes d'oppressions; thématiques; états-unis

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Basics from Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Policing the national body: Sex, race, and criminalization - Silliman, Jael Miriam; Bhattacharjee, Anannya; Davis, Angela Y.; Committee on Women, Population, and the Environment (South End Press, 2002)
Keywords: amériques; approches et analyses; corps; environnement; justice reproductive; maternité; nationalisme; racisme; régions géographiques; santé; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

La violence nazie, une généalogie européenne - Traverso, Enzo (La Fabrique, 2002)
La violence nazie ne doit rien au hasard: elle a une généalogie, qui n'est pas spécifiquement allemande, et un laboratoire, l'Europe libérale du XIXe siècle.Les camps d'extermination sont l'aboutissement d'un long processus de déshumanisation et d'industrialisation de la mort, amorcé par la guillotine et qui a progressivement intégré la rationalité du monde moderne, celle de l'usine, de la bureaucratie, de la prison. On peut trouver les origines culturelles du nazisme dans le "racisme de classe" qui triomphe après la Commune, dans le discours impérialiste sur l'"extinction des races inférieures" visant à légitimer les génocides coloniaux, enfin dans l'émergence d'une nouvelle image du juif- axée sur la figure de l'intellectuel - comme métaphore d'une maladie du corps social.Le nazisme réalisera la convergence entre ces différentes sources matérielles et idéologiques. Auschwitz se révèle ainsi - et c'est là que réside, selon Enzo Traverso, sa singularité - comme la synthèse d'un ensemble de modes de pensée, de domination et d'extermination profondément inscrits dans l'histoire occidentale.
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; approches et analyses; cours; discipline; europe; histoire; histoire et politique; pol5480; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences